From local to global HRM: interviews with HR heads in emerging Indian multinationals. (1st January 2014) - Thite, Mohan
Since the opening up of the Indian economy in early 1990s, Indian firms in general have made big strides in increasing their global competitiveness, both at home and abroad. The speed and scale of their internationalisation in the last decade are particularly note-worthy as they increase their foreign direct investment (FDI) in both the developed and developing markets. The availability and management of talent are seen to be one of their key competitive advantages. In this paper, the heads of human resources (HR) in four emerging Indian multinationals, in automotive, information technology (IT) services, bio-pharmaceutical, and conglomerates in multiple business segments, are interviewed on three main themes, namely, the evolution of HRM, the role of HRM in managing global operations/workforce and the future outlook and challenges for HRM. The interviews provide valuable insights into the state of HRM in multinationals from emerging economies and stress the need for both Western and emerging economy multinationals to learn from each other in a multi-polar world.